2019
DOI: 10.1128/jvi.00373-19
|View full text |Cite
|
Sign up to set email alerts
|

C19ORF66 Broadly Escapes Virus-Induced Endonuclease Cleavage and Restricts Kaposi’s Sarcoma-Associated Herpesvirus

Abstract: One striking characteristic of certain herpesviruses is their ability to induce rapid and widespread RNA decay in order to gain access to host resources. This phenotype is induced by viral endoribonucleases, including SOX in Kaposi's sarcoma-associated herpesvirus (KSHV), muSOX in murine gammaherpesvirus 68 (MHV68), BGLF5 in Epstein-Barr virus (EBV), and vhs in herpes simplex virus 1 (HSV-1). Here, we performed comparative transcriptome sequencing (RNA-seq) upon expression of these herpesviral endonucleases in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 59 publications
5
54
0
Order By: Relevance
“…In particular, vhs -dependent transcriptional down-regulation contributes substantially to the reduction in total RNA levels for the respective genes (Fig Q in S2 File, Fig W in S2 File). Furthermore, a recent study identified a set of 74 genes that escape degradation by four herpesviral endonucleases, including vhs [51]. Almost all of these genes were excluded from our analysis due to low expression (87%), read-in transcription (7%) or proximity to nearby genes (3%).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, vhs -dependent transcriptional down-regulation contributes substantially to the reduction in total RNA levels for the respective genes (Fig Q in S2 File, Fig W in S2 File). Furthermore, a recent study identified a set of 74 genes that escape degradation by four herpesviral endonucleases, including vhs [51]. Almost all of these genes were excluded from our analysis due to low expression (87%), read-in transcription (7%) or proximity to nearby genes (3%).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of host RNA decay factors is not sufficient to abrogate feedback between mRNA decay and Pol II occupancy muSOX expression alone is sufficient to reduce cytoplasmic populations of mRNA by 60-80% [28][29][30], and in this non-infectious setting the loss of promoter-proximal Pol II is dependent on the presence of the host RNA decay enzymes Xrn1 and Dis3L2 [25]. To determine if this mechanism is also sufficient to explain the loss of Pol II occupancy during MHV68 infection, we depleted Xrn1 and Dis3L2 individually or in tandem using siRNAs (Fig 2A).…”
Section: Accelerated Rna Decay Broadly Reduces Pol II Occupancymentioning
confidence: 99%
“…All host shutoff RNases cause global decreases in host mRNA abundance, revealed by transcriptome-wide studies [13][14][15], and display a preference for mRNAs while sparing housekeeping noncoding RNAs (ncRNAs) [12,16,17]. However, host shutoff RNases are less PLOS PATHOGENS PLOS Pathogens | https://doi.…”
Section: Selection Of Targeted and Protected Rnas And Protein/proteinmentioning
confidence: 99%
“…HSV vhs is thought to cleave most RNAs close to the 5 0 cap, with the exception of stress response mRNAs with adenylate/uridylate (AU)-rich elements in their 3 0 untranslated region (UTR), which vhs cleaves near the AU-rich element and whose 5 0 portion remains stable [28,29]. Additional complexity to the SOX targeting mechanism was revealed by the identification of SOX-resistant, or "escapee" mRNAs, which contain a structured RNA element, the "SOX resistance element" (SRE), in the 3 0 UTR [15,30,31]. The SRE recruits several host RNA binding proteins that inhibit SOX-mediated cleavage through an unknown mechanism ( Fig 1C) [30][31][32].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation